Ethnic differences in mental health among incarcerated youths: do Moroccan immigrant boys show less psychopathology than native Dutch boys? - Veen, Violaine (Springer-Verlag, 2009)
Psychiatric disorders are highly prevalent among incarcerated youth. However, whereas ethnic minority youths are overrepresented in the juvenile justice system, limited research is available on their mental health. In this study, differences in mental health problems between incarcerated adolescents of native Dutch and Moroccan origin, were examined. Child Behavior Checklist and Youth Self-Report scores were compared between incarcerated adolescents of native Dutch and Moroccan origin. Their scores were also compared to those of native Dutch and Moroccan immigrant youths in the general, non-incarcerated population. Native Dutch incarcerated adolescents showed higher levels of various mental health problems than incarcerated adolescents with a Moroccan background. Compared to the general population, incarcerated youths showed higher levels of mental health problems, but this deviation was much larger for native Dutch than for Moroccan immigrant youths. These ethnic differences in mental health problems could not be explained by ethnic differences in socio-economic background and social desirable answering tendencies. Incarcerated youths of Moroccan origin show less psychopathology than incarcerated native Dutch youths, which might be explained by disparities in sentencing procedures.